Ultimate Paris design. - Lleonart, Aitana, ....- (New York : teNeues, 2007)
This "city of light" has long been a world leader in so many ways, not least of them in design. This attractively illustrated book covers the most up-to-date Parisian design from the fields of architecture, interiors and fashion. With an in-depth round-up featuring projects for cultural, commercial, and residential spaces, we get a privileged glimpse at what's happening in this creative capital. We also are granted access to the latest developments in product design and other specialties. Browse this book for a whole host of designs by native Parisians and those who work or live here. Aitana Lleonart currently works as an editor for LOFT Publications, and freelances for various Spanish shelter magazines. She has also covered art and culture for magazines and radio. Architects: Christian de Portzamparc - Jean Nouvel - Manuelle gautrand - Christian Hauvette - Dominique Perrault - Christian Biecher.
Keywords: Architectuur -- Parijs; Parijs -- Design; Parijs -- Mode